Essays on behavioral and experimental economics - Liu, Fang (Nanyang Technological University, 2022)
There are three essays on the experimental and behavioral economics consisting of this thesis. The first essay investigates how payment modes and the lockdown during the Covid-19 pandemic interact and influence charitable donation behavior in a laboratory experiment where subjects must use either cash or contactless mobile payment to make a real donation to Singapore Red Cross. We showed that contactless mobile payment induced more donations than cash payment after the lockdown, while cash payment generated more donations than contactless mobile payment before the lockdown. People's familiarity with payment modes is crucial in explaining the payment mode effect. The pandemic makes people more accustomed to contactless mobile payment, leading to larger donations under mobile payment than cash.